Palynology of the la Veteada Formation (Lopingian) at Its Type Locality, Famatina Range, la Rioja Province, Argentina. Spores - Zavattieri, Ana Maria (2017)
This is a systematic study of the palynological assemblages 25 recorded in the upper part of the La Veteada Formation (La Veteada ssemblage). In this contribution, 38 species of trilete and monolete spores are described and/or illustrated. Two new species are described: Lundbladispora verrucosa sp. nov., and Secarisporites triangularis sp. nov., and also a new combination of Secarisporites imperialis (Jansonius) nov. comb. is proposed. The trilete spores are one of the dominant groups of the analized microflora reducing its frequency from the base to the top of the section (from 32.2 to 14.5%). Cingulate-cavate spores (derived from herbaceous lycophytes) represented by species of the genera Densoisporites-Lundbladispora, and Secarisporites are dominant. Smooth and apiculate trilete spores (derived from ferns and sphenopsids) are represented by the genera Calamospora, Punctatisporites, Granulatisporites, Brevitriletes, Cyclogranisporites, Osmundacidites, among others. The upper section of the La Veteada Formation at its type locality was deposited in fluvial-lacustrine environments under arid to semiarid climatic conditions. Semiperennial hypersaline/brackish lakes dominate the sedimentation with periodic expansion and retraction episodes suggesting a low-relief setting. In the surrounding areas of these water-bodies, dominated by evaporites, grew the vegetation mainly composed of the herbaceous lycopsids Isoetales, Selaginellales, Lycopodiales, and ferns. In the flood plain, vegetation of pteridophytes (Filicales, Zygopteridales), bryophytes and herbaceous sphenophytes developed along the river courses and in the surrounding areas of freshwater bodies (ponds and small lakes). The presence of Densoisporites complicatus, D. nejburgii, D. playfordii, D. solidus, Leptolepidites jonkerii, Lundbladispora brevicula, L. obsoleta, L. springsurensis, L. wilmotii, Ringosporites fossulatus, Secarisporites bullatus, S. imperialis, and S. lacunatus allow confirming a Lopingian age for the upper section of the La Veteada Formation. Microfloras containing high proportions of lycopsid-tetrads are commonly recorded mainly in extra-Gondwanic realm constrained to a Lopingian-early Triassic age